Age-dependent altered proportions in subpopulations of tonsillar lymphocytes - Bergler, Wolfgang; Adam, Sylvia; Gross, H.-J.; Hörmann, Karl; Schwartz-Albiez, Reinhard (Clinical & experimental immunology, 1999)
Age-related changes in functional subsets of lymphocytes may influence the potential to build up immune responses. In particular, the capacity of tonsillar lymphocytes to counter infections may be altered during ageing. In order to address this question we investigated the proportional distribution of several subsets of tonsillar T and B cells with regard to ageing. Tonsils were derived from 119 patients between 2 and 65 years of age. Lymphocyte subsets were monitored by three-colour fluorescence of relevant CD markers in flow cytometry. As a general tendency the percentage of CD3+ T cells steadily increased whereas that of CD19+ B cells decreased at the same time. No significant differences were observed between lymphocytes of patients with and without inflammatory history of the tonsils. The percentage of CD8+ T cells declined whereas that of CD4+ T cells increased during the same time span. CD45RA+ T cells increased during the first two decades of life and gradually decreased thereafter. In contrast, CD45RO+ T cells showed an opposite trend. No differences were seen in the population of CD3−/CD56+ natural killer (NK) cells. The mature B cell marker CD40 showed no significant changes during ageing. However, CD38+ B cells, representing B cells of late maturation stages, dramatically declined up to the age of 65. In a similar manner the CD5+ subpopulation of B cells decreased during ageing. Substantial changes in major tonsillar T and B cell populations as shown in this study may have an impact on the ageing process of the immune system.
Elektronische Reproduktion der Druckausgabe
Gesehen am 09.05.2022